2007
DOI: 10.1002/hipo.20263
|View full text |Cite
|
Sign up to set email alerts
|

Cav1.2, Cav1.3, and Cav2.1 in the mouse hippocampus during and after pilocarpine‐induced status epilepticus

Abstract: Calcium binding proteins are well known to be expressed by different groups of hippocampal interneurons; however, whether voltage-dependent calcium channels (Ca(v)) are also localized in these neurons, changed during and after status epilepticus (SE), and involved in epileptic activity have not been reported. In the present study, we showed the colocalization of three subtypes of voltage-gated calcium channels (Ca(v)1.2, Ca(v)1.3, or Ca(v)2.1) with different calcium binding proteins such as calbindin (CB), cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 31 publications
6
30
0
Order By: Relevance
“…In contrast, several reports have documented the expression of L-type channels in astrocytes (Akopian et al, 1996;Barres et al, 1989;D'Ascenzo et al, 2004;de Pina-Benabou et al, 2001;MacVicar, 1984;MacVicar and Tse, 1988). Interestingly, while preparing this manuscript it was reported that the expression of Ca V 2.1 is upregulated in reactive astrocytes following the induction of status epilepticus by pilocarpine (Xu et al, 2007). This finding is in line with a possible involvement of P/Q-type channels in astrogliosis.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…In contrast, several reports have documented the expression of L-type channels in astrocytes (Akopian et al, 1996;Barres et al, 1989;D'Ascenzo et al, 2004;de Pina-Benabou et al, 2001;MacVicar, 1984;MacVicar and Tse, 1988). Interestingly, while preparing this manuscript it was reported that the expression of Ca V 2.1 is upregulated in reactive astrocytes following the induction of status epilepticus by pilocarpine (Xu et al, 2007). This finding is in line with a possible involvement of P/Q-type channels in astrogliosis.…”
Section: Discussionsupporting
confidence: 48%
“…Reactive astrocytes show increased expression of L-type Ca 21 channels in several models of CNS trauma, such as ischemia, anoxia, kainic acid-induced epilepsy, mechanical and thermal lesions, and hipomyelination (Brown et al, 2001;Chung et al, 2001;Westenbroek et al, 1998). More recently, the upregulation of the specific calcium channel subunits Ca V 1.3 and Ca V 2.1 has been described in reactive astrocytes following pilocarpine-induced epilepsy (Xu et al, 2007). Significantly, astrogliosis can be attenuated by L-type Ca 21 channel blockers both in cultured astrocytes (Lee et al, 2000;Oh et al, 1995) and in vivo models of CNS injury (Agrawal et al, 2000;Du et al, 1999;Klepper et al, 1995).…”
Section: Introductionmentioning
confidence: 97%
“…A subset of astrocytes in the hippocampus indeed expresses Cav1.3 (Fig. 2g) [46,59], and upregulation of Cav1.3 has been demonstrated in reactive astrocytes of the mouse hippocampus after pilocarpine-induced status epilepticus [60]. Thus, Cav1.3 may contribute to volume regulation and modulation of the activity state of astrocytes in the hippocampus and could be involved in astrogliosis in chronic neurodegenerative disorders such as Alzheimer´s disease or in acute CNS lesions such as spinal cord injury.…”
Section: Discussionmentioning
confidence: 95%
“…Although these are likely mediated by Cav channel dysfunction in neurons, astrocytes may also play a role in disease processes. Cav1.3 (L-type) and Cav2.1 (P-type) channel expression is induced in hippocampal reactive astrocytes following pilocarpine-induced status epilepticus [104]. In APP transgenic mice, Cav1.2 channels are induced in reactive astrocytes surrounding amyloid plaques, and their expression increases with the age of mice and the number of plaques [105].…”
Section: Astrocyte Channel Proteinsmentioning
confidence: 99%